Vasospasm or Atherosclerotic Lesion of Coronary Arteries: Case Management - Tashchuk, V. K.; Makoviichuk, I. O.; Al Salama, M. V.; Malinevska-Biliichuk, O. V.; Biletskiy, S. S.; Lisovenko, A. A. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Background. Coronary artery vasospasm (CVS) is an important mechanism of myocardial ischemia which can produce any of the manifestations of coronary artery disease from silent myocardial ischemia to acute coronary syndrome including myocardial infarction or sudden cardiac death. One of the main markers of CVS is retrosternal pain not associated with increased myocardial oxygen requirement such as that due to exercise or emotional excitement with frequent attacks in the morning and temporary ST segment elevation. Some patients have variant angina caused by the spasm of coronary arteries (СА) coupled with stable angina provoked by emotional and physical stress. Such patients have decreased exercise tolerance. Aim. To determine the feasibility and subsequence of the appointment of diagnostic procedures such as electrocardiography (ECG), bicycle ergometry (BEM), provocative tests and coronary angiography and left ventriculography (CAG & LVG) in order to visualize СА, to make the choice of patient’s management and to assign an adequate therapeutic program. Materials and methods. The patient who was admitted with complaints about progression of angina and shortness of breath received the full complex of diagnostic manipulations. The purpose was to verify the diagnosis and to prescribe an adequate treatment. Results. This clinical case shows the subsequence of the appointment of diagnostic procedures to the patient who has normal ECG, ST segment elevation on BEM and progression of angina attacks, that is, the necessity of the widespread introduction of coronary angiography. Conclusion. This article shows the necessity of appointment of CAG & LVG. CAG & LVG revealed atherosclerotic lesion of CA which caused chest paint, ST segment elevation, and this result confounded the presence of CVS as a cause of complaints in this patient. The patient underwent stenting of the affected CA which helped to eliminate the cause of pain and is compatible with adequate therapeutic tactics for patients with CA stenosis.